Expert specification of the ACMG/AMP variant interpretation guidelines for genetic hearing loss. Issue 11 (11th October 2018) - Oza, Andrea M.; DiStefano, Marina T.; Hemphill, Sarah E.; Cushman, Brandon J.; Grant, Andrew R.; Siegert, Rebecca K.; Shen, Jun; Chapin, Alex; Boczek, Nicole J.; Schimmenti, Lisa A.; Murry, Jaclyn B.; Hasadsri, Linda; et al.
Abstract: Due to the high genetic heterogeneity of hearing loss (HL), current clinical testing includes sequencing large numbers of genes, which often yields a significant number of novel variants. Therefore, the standardization of variant interpretation is crucial to provide consistent and accurate diagnoses. The Hearing Loss Variant Curation Expert Panel was created within the Clinical Genome Resource to provide expert guidance for standardized genomic interpretation in the context of HL. As one of its major tasks, our Expert Panel has adapted the American College of Medical Genetics and Genomics/Association for Molecular Pathology (ACMG/AMP) guidelines for the interpretation of sequence variants in HL genes. Here, we provide a comprehensive illustration of the newly specified ACMG/AMP HL rules. Three rules remained unchanged, four rules were removed, and the remaining 21 rules were specified. These rules were further validated and refined using a pilot set of 51 variants assessed by curators and disease experts. Of the 51 variants evaluated in the pilot, 37% (19/51) changed category based upon application of the expert panel specified rules and/or aggregation of evidence across laboratories. These HL‐specific ACMG/AMP rules will help standardize variant interpretation, ultimately leading to better care for individuals with HL. Abstract : The Hearing Loss Variant Curation Expert panel was created within ClinGen with the goals of standardizing variant interpretation in hearing loss, resolving existing discrepancies in submitted variant classifications in ClinVar and providing expert variant classifications for hearing loss. Here we present specifications of the ACMG/AMP variant interpretation guidelines for hearing loss and the results of a pilot project in which these specifications were applied to 51 variants in the CDH23, COCH, GJB2, KCNQ4, MYO6, MYO7A, SLC26A4, TECTA, and USH2A genes.